Impact of the covid-19 pandemic on the changes in dietary habits, lifestyle and physical activity in the Slovak population - Marta Lorková; Martina Gažarová (National Institute of Public Health - National Institute of Hygiene, 2023)
Background: The COVID-19 pandemic caused by the coronavirus was accompanied by the emergence of various adverse conditions, as well as the deterioration of health from the point of view of chronic diseases, as well as lifestyle changes related to the preference of certain foods and changes in body weight due to the restriction of free movement. Objective: The objective of our survey was to assess the impact of the pandemic and lockdown on selected key lifestyle elements affecting the overall health status of the Slovak population and subsequently to evaluate subjectively assessed changes in the respondents' eating habits, daily routine, physical activity and body weight. Material and Methods: The research group consisted of 528 participants who took part in an online distributed questionnaire survey. Results: Respondents subjectively evaluated the change in lifestyle rather negatively. Up to 48.37% of men and 38.93% of women reported a change for the worse. Almost 59% of participants reported no change in their health, while almost a quarter reported a slight deterioration in their health. A change in eating habits for the worse was reported by 22.88% of men and 28.26% of women (p<0.05). Increased appetite during the lockdown was reported by 24.18% of men and 35.47% of women (p<0.05), more frequent overeating during the pandemic occurred in 30.07% of men and 38.13% of women. When evaluating the consumption of individual food commodities, the increased consumption of fresh fruit, fresh vegetables (p<0.01), homemade bread (p<0.05), homemade pastries (p<0.05) and dairy products (p<0.05) is very favourable. We also found a significant increase in the consumption of sweets (p<0.01) and coffee (p<0.001). When evaluating the sleep pattern, we noted an increase in sleep during the pandemic, as well as more time spent sitting. Over half of the respondents reported a change in body weight, in most cases it was an increase in both sexes. Conclusions.: The results show that the pandemic and the restrictions during it caused changes not only in diet, but also in physical activity, daily routine and overall lifestyle. However, this is a very specific issue that needs to be assessed in a comprehensive and strictly personalized manner. The positive or negative impact of the pandemic on the health of the population will be the subject of research in the near future.